Assessing the Importance of Internal and External Self-Esteem and Their Relationship to Honor Concerns in Six Countries. (December 2020) - van Osch, Yvette; Bender, Michael; He, Jia; Adams, Byron G.; Kunuroglu, Filiz; Tillman, Richard N.; Benítez, Isabel; Sekaja, Lusanda; Mamathuba, Neo
We assessed empirical support for (a) the widely held notion that across so-called "honor, dignity, and face cultures, " internal and external components of self-esteem are differentially important for overall self-esteem; and (b) the idea that concerns for honor are related to internal and external components of self-esteem in honor cultures but not in dignity and face cultures. Most importantly, we also set out to (c) investigate whether measures are equivalent, that is, whether a comparison of means and relationships across cultural groups is possible with the employed scales. Data were collected in six countries ( N = 1, 099). We obtained only metric invariance for the self-esteem and honor scales, allowing for comparisons of relationships across samples, but not scale means. Partly confirming theoretical ideas on the importance of internal and external components of self-esteem, we found that only external rather than both external and internal self-esteem was relatively more important for overall self-esteem in "honor cultures"; in a "dignity" culture, internal self-esteem was relatively more important than external self-esteem. Contrary to expectations, in a "face" culture, internal self-esteem was relatively more important than external self-esteem. We were not able to conceptually replicate earlier reported relationships between components of self-esteem and the concern for honor, as we observed no cultural differences in the relationship between self-esteem and honor. We point toward the need for future studies to consider invariance testing in the field of honor to appropriately understand differences and similarities between samples.